Disability and Spirituality: Re-Membering Wholeness in Services and Supports - Gaventa, William C. (Journal of disability & religion, 2016)
Spirituality has received scant attention in scientific research, policy development, and service provision in relationship to intellectual and developmental disabilities, yet the importance of self-determination, community inclusion, and natural supports points to its importance as a component of holistic care, as well as a crucial component of cultural attitudes and values. The goal of this article, presented as a master lecture at the 2016 International Association for the Scientific Study of Intellectual and Developmental Disabilities Global Congress, Melbourne, Australia, is to demonstrate the foundational connections between disability and spirituality, summarize current research, and advocate for inclusive research and practice. Current definitions of disability lead into the core dimensions of personal and social constructs. To define spirituality, one ends up in the search for meaning in the face of limitations and vulnerability and in questions of identity, purpose, and community. Both paths lead to one another in theory and, as current research indicates, in practice and thus to a rationale for collaborative practice, policy, and research that leads to more effective and holistic supports and services. Ignoring spirituality is unscientific, and ignoring scientific perspectives is unfaithful.